A comparative study between manual vacuum aspiration and electrical vacuum aspiration for the first trimester medical termination of pregnancy - Samal, Sunil K.; Rathod, Setu; Padhi, Maya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of this study is to compare the manual vacuum aspiration (MVA) and electrical vacuum aspiration (EVA) as the method for first trimester medical termination of pregnancy (MTP) in terms of efficacy, blood loss, duration, acceptability and complications. The study also compares paracervical block (PCB) and intramuscular sedation (IMS) i.e., injection pentazocine 30 mg and injection promethazine 25 mg as pre-operative analgesia for both the MTP procedures. Methods: The present study was conducted in the postpartum center and department of Gynecology and Obstetrics, SCB Medical College, Cuttack. A total 200 patients were studied of which randomly selected 100 patients underwent MVA and remaining 100 patients underwent EVA. Cases were compared with respect to their age, parity, blood loss, time taken and complications. Results: In the present study, MVA was effective in 97% and EVA in 98% cases. Thus, the two procedures did not show much difference as far as their effectiveness was concerned. Comparing intra and post-operative pain, PCB was significantly more effective in reducing pain as compared to IMS. Conclusions: MVA has a safety and efficacy profile similar to that of EVA. Furthermore, MVA is a simple, safe, effective procedure, portable and low cost technique. Hence, MVA is a promising method compared to EVA and can be practiced widely in rural areas where access to medical facilities are limited, high-tech equipments were not available and the power supply was erratic and maintenance of instruments were not up to the mark. The judicious use of MVA comes with a promise to make early abortions safe and easily accessible to women of both rural and urban societies belonging to any socio-economic strata.